Non-ST-elevation myocardial infarction hiding behind myopericarditis in a patient with systemic lupus erythematosus. Issue 2 (25th February 2022) - Freeman, Howard; Lutz, Katherine; Riquelme, Patricio; Kahl, Leslie
Abstract : Systemic lupus erythematosus (SLE) is a chronic inflammatory condition with various cardiovascular sequelae. Pericarditis is the most common cardiac manifestation, yet patients also have a markedly elevated risk of premature atherosclerosis and acute coronary syndrome (ACS). This makes the diagnosis of ischaemic chest pain both challenging and crucial in these patients. Here, we examine the case of a 39-year-old male who presented with acute myopericarditis and pericardial tamponade in the setting of newly diagnosed SLE. Several days later, the patient experienced an infero-septal non-ST-elevation myocardial infarction. Urgent percutaneous coronary intervention showed 100% proximal right coronary artery (RCA) occlusion with subsequent placement of two overlapping drug-eluting stents to the proximal-mid RCA. This case illustrates the need to carefully evaluate patients with SLE for underlying cardiovascular disease regardless of age or the presence of tradition risk factors. Recognition of the increased incidence of ACS in SLE patients is crucial for early diagnosis and revascularisation.